A novel approach to concentrate human and animal viruses from wastewater using receptors-conjugated magnetic beads. (1st April 2022) - Oh, Chamteut; Kim, Kyukyoung; Araud, Elbashir; Wang, Leyi; Shisler, Joanna L.; Nguyen, Thanh H.
Highlights: PGM-MBs efficiently concentrate human and animal viruses from wastewater. Heat denaturation is compatible with the PGM-MBs to extract viral genomes. Environmental PCR inhibitors do not inhibit the qPCR reactions. The PGM-MBs method can be used for surveillance of SARS-CoV-2 in wastewater. The PGM-MBs method cost less than 0.5 USD per 10 mL of sewage. Abstract: Viruses are present at low concentrations in wastewater; therefore, an effective method for concentrating virus particles is necessary for accurate wastewater-based epidemiology (WBE). We designed a novel approach to concentrate human and animal viruses from wastewater using porcine gastric mucin-conjugated magnetic beads (PGM-MBs). We systematically evaluated the performances of the PGM-MBs method (sensitivity, specificity, and robustness to environmental inhibitors) with six viral species, including Tulane virus (a surrogate for human norovirus), rotavirus, adenovirus, porcine coronavirus (transmissible gastroenteritis virus or TGEV), and two human coronaviruses (NL63 and SARS-CoV-2) in influent wastewater and raw sewage samples. We determined the multiplication factor (the ratio of genome concentration of the final solution to that of the initial solution) for the PGM-MBs method, which ranged from 1.3 to 64.0 depending on the viral species. Because the recovery efficiency was significantly higher when calculated with virus titers than it was with genome concentration, the PGM-MBs method could be an appropriate tool for assessing the risk to humans who are inadvertently exposed to wastewater contaminated with infectious viruses. Furthermore, PCR inhibitors were not concentrated by PGM-MBs, suggesting that this tool will be successful for use with environmental samples. In addition, the PGM-MBs method is cost-effective (0.5 USD/sample) and has a fast turnaround time (3 h from virus concentration to genome quantification). Thus, this method can be implemented in high throughput facilities. Because of its strong performance, intrinsic characteristics of targeting the infectious virus, robustness to wastewater, and adaptability to high throughput systems, the PGM-MBs method can be successfully applied to WBE and ultimately provides valuable public health information. Graphical abstract: Image, graphical abstract